Écriture(s) de mémoires à quatre mains : les deux Robbe-Grillet - José María Fernández Cardo (Carnets)
The writing of memoirs is treated in this article as a joint work -dual writing-, that of Alain Robbe-Grillet and his wife Catherine Robbe-Grillet. Both, writers of novels at the beginning and then singular memorialists, cultivated genres related to the expression of intimacy as diverse as autofiction, the journal, correspondence by letters or the biographical dictionary. These texts, undoubtedly going beyond the purely documentary status with a view to the construction of a sustained biographical discourse, themselves testify to an enormous capacity for significance through the practice of new generic registers of the narrative, oriented towards the writing of the self.